Electron injection study of photoexcitation effects on supported subnanometer Pt clusters for CO2 photoreduction. Issue 23 (31st May 2018) - Yang, Chi-Ta; Wood, Brandon C.; Bhethanabotla, Venkat R.; Joseph, Babu
Abstract : Upon the injection of electrons, supported Pt clusters stabilize the adsorption of bent-form CO2 species and facilitate the formation of CO2 − anions. Abstract : Using density functional theory, we study the effect of injected electrons (simulating photoexcited electrons) on the energetics, structures, and binding sites available to CO2 molecules on subnanometer Pt clusters decorated onto anatase TiO2 (101) surfaces, shedding light on the first and key step of CO2 photoreduction. Upon the addition of one, two, or three electrons, the O–C–O angles of adsorbed CO2 become progressively smaller in binding sites that directly contact Pt clusters, while no significant change is found in the intra bond length of the adsorbed CO2 and in the bonding distances between the adsorbed CO2 and supported clusters. The extra electrons lead to the stabilization of adsorption sites identified on neutral slabs, including previously metastable configurations, suggesting the enhancement of accessible CO2 binding sites. Furthermore, supported clusters are able to populate the electronic states of adsorbed CO2 species, facilitating the formation of the CO2 − anion. To help interpret experimentally observed frequencies, conversion factors are proposed to gain insight into the charge state and O–C–O angle of the adsorbed CO2 . Interestingly, upon electron addition, cluster reconstruction may exist due to the bonding inclination between CO2 and atoms in the Pt cluster, further stabilizing the intermediate complexes. Finally, the rate-limiting step (C–O bond cleavage) in the CO2 dissociation to CO is slightly reduced by the introduction of an extra electron. Our results show that subnanometer metal cluster based photocatalysts are good candidates for CO2 photoreduction.